Chlorogenic Acid Attenuates Oxidative Stress-Induced Intestinal Mucosa Disruption in Weaned Pigs - Chen, Jiali; Chen, Daiwen; Yu, Bing; Luo, Yuheng; Zheng, Ping; Mao, Xiangbing; Yu, Jie; Luo, Junqiu; Huang, Zhiqing; Yan, Hui; He, Jun (Frontiers in Veterinary Science, 2022)
Chlorogenic acid (CGA) is a natural polyphenol that possesses potent antioxidant activity. However, little is known about its exact role in regulating the intestinal health under oxidative stress. This study was conducted to explore the effect of dietary CGA supplementation on intestinal barrier functions in weaned pigs upon oxidative stress. Twenty-four weaned pigs were allocated to three treatments and were given a basal diet (control) or basal diet containing CGA (1,000 mg/kg) for 21 days. Pigs were challenged by sterile saline (control) or diquat [10 mg/kg body weight (BW)] on the 15th day. Results showed that CGA attenuated the BW reduction, reduced the serum concentrations of diamine oxidase and D-lactate, and elevated serum antioxidant enzymes activities in diquat-challenged weaned pigs (P < 0.05). Moreover, diquat challenge decreased villus height and activities of sucrase and alkaline phosphatase in jejunum and ileum (P < 0.05), but CGA elevated the villus height and enzyme activities in the intestinal mucosa (P < 0.05). In addition, CGA not only decreased the expression levels of Bax, caspase-3, and caspase-9 (P < 0.05) but also elevated the expression levels of sodium glucose transport protein-1, glucose transporter-2, occludin, claudin-1, zonula occludens-1, and antioxidant genes such as nuclear factor erythroid-derived 2-related factor 2 and heme oxygenase-1 in intestinal mucosa of weaned pigs upon oxidative stress (P < 0.05). These findings suggested that CGA can attenuate oxidative stress-induced growth retardation and intestinal mucosa disruption, which was linked to elevated antioxidative capacity and enhanced intestinal barrier integrity.